Performance Evaluation of Co-Design of Discrete Event Networked Controlled DC Motor System - Jain, Ankur; K. Roy, B (International Journal of Engineering and Technology, 2018)
In this paper, we have designed a control technique for a networked DC motor in the presence of networked delay, packet loss, and jitter. We have used the predicted states for the controller design to achieve the transient and steady-state objectives. A networked compensator is designed to overcome the network constraints. The network link is modelled using the queue server mechanism which can assimilate a lot of features of the network. The proposed technique can also be applied to various other applications. The analysis of the networked control system is done in frequency and time domains. The simulation results are presented to test the performance of the proposed control technique.Â